کرونا وائرس میں مجوزہ احتیاطی تدابیر اور اسلامی تعلیمات : Preventive Measures for Corona Virus and Islamic Teachings - Dr. Muhammad Ramazan Najam Barwi; Dr. Ammara Rehman (Al Basirah, 2022)
The Sīrah of the Holy Prophetﷺ is the base of guidance for a man of every age. Through study of the Sīrah in perspective of the problems of the present time proves to be a practicable solution today as it was practicable centuries ago. Corona virus has become disastrous for the whole world and has adverse on every field of the life. The experts of medical sciences have suggested a few safety measures to avoid it. But the study of the Sīrah of the Holy Prophet ﷺ tells that these all safety measures are available in the practical life of the Holy Prophetﷺ and He also encouraged His followers to follow these measures. In this situation it can be said that the experts of medical science of present time have received their results of SOPs about corona virus and other infectious diseases from the Sīrah of the Holy Prophet ﷺ and his sayings.